Information technology and organizations strategies, networks, and integration - Bloomfield, Brian P. (Oxford University Press, 2011)
This text covers IT in organizations - how it works, how it changes organizations and the problems and challenges it creates. Based on detailed research in several sectors (including financial services and hospitals), the authors present an analysis of various issues